Muhammad Thalib, Majelis Mujahidin Indonesia, dan Tafsir Ayat-ayat Penegakan Syariat Islam di Indonesia - Anwar Kurniawan; Ahmad Aminuddin (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2018)
Majelis Mujahidin Indonesia (MMI/The Indonesian Mujahedeen Council) is an Islamic organization, which demands the implementation of sharī‘ah in Indonesia. Muhammad Thalib, the leader of MMI, is a figure who also concerns about the Quranic interpretation. He frequently interprets the Quranic verses on his works within political nuance in relation to MMI’s ideology. This article aims to identify Thalib’s interest and the extent of his ideological tendency. His published works in a number of media are the main source of the data elaborated in this article. This article argues that Thalib’s interpretation of the Quranic verses comprises two political interests. Firstly, the interpretation attempts to convince the reader to believe that the implementation of sharī‘ah is undoubtedly urgent. Secondly, sharī‘ah seems to be perceived as the main objective, colored with political nuance, and it has been reduced for this main purpose in order to make Muslims “find” God. In other words, Thalib’s interpretation of the Quranic verses puts sharī‘ah as a means of political maneuver. It seems that through his interpretation, Thalib attempts to challenge, while at the same time protects himself from, his opponents.